2009
DOI: 10.1007/s10815-009-9331-9
|View full text |Cite
|
Sign up to set email alerts
|

Is caspase inhibition a valid therapeutic strategy in cryopreservation of ovarian tissue?

Abstract: Purpose The aim of this study is to determine whether inclusion of caspase inhibitor can improve the efficacy of cryopreservation of ovarian tissue. Methods Mice were randomly assigned to the Group A (fresh control group) Group B (inclusion of caspase inhibitor) and Group C (non-inclusion of caspase inhibitor). Ovarian tissue in Group B and Group C was vitrifiedthawed. TUNEL assay and Bax protein detection were measured after cryopreservation. The mice in all groups received autotransplantation. The number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…Nevertheless, a prolonged exposure with high concentrations of low molecular weight CPAs such as DMSO during the vitrification technique causes severe toxicity (Yavin & Arav, 2007) compared with the slow freezing methodology. DMSO at high concentrations is known to potentially activate the apoptotic caspase pathway (Zhang et al, 2009). Therefore, the combination of DMSO with another CPA with rapid penetration and less toxicity such as ethylene glycol (EG) may be an alternative to vitrification medium containing only high concentrations of DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a prolonged exposure with high concentrations of low molecular weight CPAs such as DMSO during the vitrification technique causes severe toxicity (Yavin & Arav, 2007) compared with the slow freezing methodology. DMSO at high concentrations is known to potentially activate the apoptotic caspase pathway (Zhang et al, 2009). Therefore, the combination of DMSO with another CPA with rapid penetration and less toxicity such as ethylene glycol (EG) may be an alternative to vitrification medium containing only high concentrations of DMSO.…”
Section: Introductionmentioning
confidence: 99%
“…HGL5 COV434 In previous studies, it was demonstrated that the short-term culture of pancreatic islets and mice ovarian cortex cryopreserved with Z-VAD-FMK reduced post-transplantation apoptosis and subsequently improved the outcome of grafts [37,34]. Moreover, Z-VAD-FMK has been found to abolish the ischemia-mediated activation of caspases [35].…”
Section: Gc1amentioning
confidence: 99%
“…While the ability of S1P to protect follicles from chemotherapy and radiationinduced damages has been well demonstrated [25][26][27][28][29], the protective effects of S1P in cryopreserved tissue grafting studies remain controversial [30][31][32][33]. Another alternative, a permeable synthetic peptide pan-caspase inhibitor, benzyloxycarbonyl-Val-Ala-Asp-fluoromethyl ketone (Z-VAD-FMK), has only been studied once in a xenograft model of cryopreserved ovarian tissue after producing encouraging results as a therapeutic option [34]. Z-VAD-FMK has also been identified as an efficient caspase inhibitor to prevent ischemia/reperfusion injuries in the liver [35], brain [36], and pancreas [37].…”
Section: Introductionmentioning
confidence: 99%
“…The supplement DHEA increased the number of follicles in aged mice, and particularly the number of primordial and primary follicles. This effect was presumably achieved by inhibiting follicular atresia (35). Anti-γH 2 AX staining indicated that atretic follicles were rescued by suppressing DNA double-strand breaks (36).…”
Section: Discussionmentioning
confidence: 99%
“…At least 30 slides from 5 mice in each group were stained with TUNEL to obtain data on follicular atresia. Follicles were considered TUNEL-positive if either the oocyte alone, the oocyte and GCs, or oocytes were negative but > 50% of GCs were positive (35). The percentage of TUNEL-positive follicles was manually calculated by two independent blinded examiners using the Olympus Scanner.…”
Section: Tunel Stainingmentioning
confidence: 99%